Identification of New, Translatable ProtectomiRs against Myocardial Ischemia/Reperfusion Injury and Oxidative Stress: The Role of MMP/Biglycan Signaling Pathways - Tamara Szabados; Arnold Molnár; Éva Kenyeres; Kamilla Gömöri; Judit Pipis; Bence Pósa; András Makkos; Bence Ágg; Zoltán Giricz; Péter Ferdinandy; Anikó Görbe; Péter Bencsik (MDPI AG, 2024)
Introduction: Ischemic conditionings (ICon) were intensively investigated and several protective signaling pathways were identified. Previously, we have shown the role of matrix metalloproteinases (MMP) in myocardial ischemia/reperfusion injury (MIRI) and the cardioprotective role of biglycan (BGN), a small leucine-rich proteoglycan in vitro. Here, we hypothesized that cardiac MMP and BGN signaling are involved in the protective effects of ICon. Methods: A reverse target-microRNA prediction was performed by using the miRNAtarget™ 2.0 software to identify human microRNAs with a possible regulatory effect on MMP and BGN, such as on related genes. To validate the identified 1289 miRNAs in the predicted network, we compared them to two cardioprotective miRNA omics datasets derived from pig and rat models of MIRI in the presence of ICons. Results: Among the experimentally measured miRNAs, we found 100% sequence identity to human predicted regulatory miRNAs in the case of 37 porcine and 24 rat miRNAs. Upon further analysis, 42 miRNAs were identified as MIRI-associated miRNAs, from which 24 miRNAs were counter-regulated due to ICons. Conclusions: Our findings highlight 24 miRNAs that potentially regulate cardioprotective therapeutic targets associated with MMPs and BGN in a highly translatable porcine model of acute myocardial infarction.